2008
DOI: 10.1001/archinte.168.11.1174
|View full text |Cite
|
Sign up to set email alerts
|

25-Hydroxyvitamin D and Risk of Myocardial Infarction in Men<subtitle>A Prospective Study</subtitle>

Abstract: Background: Vitamin D deficiency may be involved in the development of atherosclerosis and coronary heart disease in humans. Methods: We assessed prospectively whether plasma 25hydroxyvitamin D (25[OH]D) concentrations are associated with risk of coronary heart disease. A nested casecontrol study was conducted in 18 225 men in the Health Professionals Follow-up Study; the men were aged 40 to 75 years and were free of diagnosed cardiovascular disease at blood collection. The blood samples were re

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
705
6
27

Year Published

2009
2009
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 1,061 publications
(763 citation statements)
references
References 56 publications
(34 reference statements)
25
705
6
27
Order By: Relevance
“…This is in line with prospective population-based studies which showed that low 25(OH)D levels are an independent risk factor for cardiovascular events and cardiovascular mortality [101][102][103]. We are aware that discussing the causality of vitamin D deficiency for chronic diseases is a difficult task because sun exposure is the main determinant of vitamin D status and is usually inversely correlated with the severity of illness.…”
Section: Clinical Consequences and Summarysupporting
confidence: 77%
“…This is in line with prospective population-based studies which showed that low 25(OH)D levels are an independent risk factor for cardiovascular events and cardiovascular mortality [101][102][103]. We are aware that discussing the causality of vitamin D deficiency for chronic diseases is a difficult task because sun exposure is the main determinant of vitamin D status and is usually inversely correlated with the severity of illness.…”
Section: Clinical Consequences and Summarysupporting
confidence: 77%
“…Vitamin D has been reported to improve endothelial function and insulin resistance in diabetic patients (37) . Serum 25(OH)D has been reported to be associated with the risk for CVD, including hypertension, IHD, heart failure and mortality from these diseases (11,13,(38)(39)(40) . In contrast, some population-based studies have not shown an independent contribution by serum 25(OH)D concentration in metabolic syndrome (41,42) , and other small-scale intervention studies have found that vitamin D supplementation has no effect on insulin resistance or sensitivity (43)(44)(45) .…”
Section: Discussionmentioning
confidence: 99%
“…(5) Regarding general health endpoints, the Endocrine Society states that while evidence from randomized controlled trials is lacking, numerous epidemiological studies have suggested that a 25(OH)D blood level of 30 ng/mL and above may have additional health benefits in reducing the risk of common cancers, autoimmune diseases, type 2 diabetes, cardiovascular disease, and infectious diseases. (6)(7)(8)(9)(10) In contrast, the IOM concludes that there is no evidence that a 25(OH)D threshold greater than 20 ng/mL has any benefit to health. (11) Although no consensus has been achieved as to whether 20 ng/mL or 30 ng/mL is the optimal threshold of vitamin D, as reflected in these most recent recommendations, most agree that many people are vitamin D-deficient and need vitamin D supplements to meet their vitamin D requirement.…”
Section: Esirable Thresholds For 25(oh)d Have Been Discussedmentioning
confidence: 99%